Empowering Families of Indonesian Migrant Workers through Basic Financial Literacy Programme in Padamara Village - Sobirin, Muhammad Khozin; Assakina, Laena; Amali, Muhammad Farhi Roza; Prameswari, Baiq Arizayana; Makhroja, Mega Nisfa; Rizki, Khairur (Prospect Publishing, 2024)
Empowerment of Migrant Worker families is not only about education, procedural departure mechanisms, but also about financial management literacy for Migrant Worker families so that the remittances received are used optimally. Financial management needs to be very important for Migrant Workers, this is because with financial management literacy, the families of Indonesian Migrant Workers can manage their finances and produce a result from remittances to achieve economic stability. This research was conducted in Padamara Village, Sukamulia District, East Lombok. This research used a qualitative approach in the form of surveys, interviews, documentation of activities, socialisation, and assistance to the community directly. The socialisation was accompanied by resource persons who are competent in this matter, namely the Indonesian Migrant Workers Protection Service Centre (BP3MI) and Bank Rakyat Indonesia (BRI). The results of this study prove that the people of Padamara Village do not fully understand basic financial management literacy, basic financial literacy socialisation and mentoring have a positive influence on the community in financial matters. This is evidenced by the understanding of the community in managing their finances at the time of the mentoring activities.